PROFIL KESULITAN MAHASISWA BIMBINGAN DAN KONSELING DALAM BERINTERAKSI SOSIAL - Arya Duta Erwinsah; Suryadi; Rici Kardo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the fact that some students experience difficulties in social interaction. This is evident in their behavior of not greeting each other when passing each other, avoiding group activities due to discomfort and feeling confused when expressing opinions, and a tendency to isolate themselves. The purpose of this study was to describe: difficulties in social interaction, social anxiety, lack of interpersonal communication skills, feelings of inferiority or low self-esteem, social isolation, difficulties in social adaptation, and dependence on technology. This research was conducted using a quantitative descriptive method. The population of this study was 307 guidance and counseling students. The sampling technique used was random sampling, with 66 students. The data collection instrument used was a questionnaire, and the data analysis technique used was descriptive analysis. The results of this study indicate that the profile, 1). Difficulty in social interaction seen from the indicator of students' social anxiety is in the fairly high category, 2). Difficulty in social interaction seen from the indicator of students' lack of interpersonal communication skills is in the fairly high category. 3). Difficulty in social interaction seen from the indicator of students' feelings of inferiority or low self-esteem is in the fairly high category. 4). Difficulty in social interaction seen from the indicator of students' social isolation is in the fairly high category. 5). Difficulty in social interaction seen from the indicator of students' adaptation difficulties is in the fairly high category. 6). Difficulty in social interaction seen from the indicator of students' dependence on technology is in the fairly high category. Based on the results of the study, it is recommended that students improve their social interaction difficulties